DIRECTED READING THINKING ACTIVITY (DR-TA) STRATEGY TO TEACH READING - Seftika, Seftika (STKIP Muhammadiyah Pringsewu, 2016)
This study aims to investigate the implemetation of Directed Reading Thinking Activity(DR-TA) in enhancing studentsâ reading comprehension. The process of DR-TAincludes predicting, reading, and proving. This study employed quasi experimetaldesign. As the lecturer guides the process, the DRTA teaches students to determine thepurpose for reading and make adjustments to what they think will come next based onthe text. The finding shows that studentsâ reading comprehension increased afterapplying Directed Reading Thinking Activity( DR-TA). By using this strategy studentscan activate their prior knowledge of a topic/content of the text to be read, hypothesizeabout what might be addressed in the text, and establish meaningful purposes forreading the text.Keywords: Directed Reading Thinking Activity strategy, reading, comprehension.